An analysis of the 2014 New Zealand general election: do Internet use and online party mobilisation matter?. (2nd January 2019) - Tsai, Chia-Hung; Tan, Alexander C.; Jung, Koochul
ABSTRACT: Like many advanced industrial democracies, New Zealand has been experiencing relatively stagnant voter turnout levels. Much of the blame for low voter turnout has been directed towards voter apathy. The rapid development of Internet and communications technologies has made scholars consider the Internet as a possible remedy for the participation bias. In this research note, we extend the examination of Internet and vote mobilisation to the case of New Zealand. We ask whether the mobilisation by political parties and other people using the new media makes a difference in voter turnout. Specifically, we are interested in whether political parties mobilising citizens by using the new media and/or virtual methods make a difference to voter turnout. Using the 2014 New Zealand General Election as the basis of our analysis, we find that use of the Internet increases the probability of casting a vote. Moreover, we find that if Internet use is complemented by a party orientation, voters are more likely to vote as well. While we do not find support for party campaigning through the Internet in increasing the probability of voting, these findings give support to claims that the Internet enhances political participation.